Budaya Longko' pada Masyarakat Toraja dalam Perspektif Etika - Alvriana Ratanna; Mrs. Nurlela (Rayhan Intermedia, 2023)
This study aims to determine the process of Longko' culture forming the ethics of the Toraja people, the views of the Toraja people on longko culture, and what values ​​are contained in longko' culture. This study used a qualitative type with the technique of determining the informants selected by purposive sampling with a total of 6 research informants namely religious leaders, traditional leaders and the people of Toraja. Data collection is done through observation, interviews, and documentation. The results of this study indicate that: 1) Longko' culture concerns community ethics, concerns feelings and self-esteem where the longko' culture has been instilled by parents in each individual to behave, behave politely, respect and not treat parents. 2) Longko' culture which means dignity and society views this longko' culture positively with enthusiasm and hard work, and is able to give a good influence and there is an ingrained feeling of shame for not doing things that are not good and or not doing things carelessly. 3) Longko' culture has self-awareness values, politeness values ​​such as greeting when meeting, kissing parents' hands when saying goodbye, human values ​​such as respecting parents, maintaining the good name of the family, obeying parents' advice, the dignity and value of tongkonan, family values, for example, attitudes of trust and values ​​that come from oneself.